Mapping the social responsibility of small business as discourse and practice: an investigation of African and Caribbean microbusinesses in London and Nottingham, UK - Udueni, Igho Anthony (2011)
Increasing globalisation, neoliberal policies and migration inflows have in the last few decades transformed the United Kingdom into a largely cosmopolitan nation with a varied and growing population of ethnic minority owned and/or managed businesses. There is however very little knowledge of how the imperatives of social responsibility resonate within this ever expanding cluster of ethnic minority businesses.